Legends, Children’s Tales, and Detective Stories: Common Threads in Emily Santa-Cruz’s Literary Production (2022)
The research focuses on studying the main threads detected in the prose work of the writer Emily Santa-Cruz. In the first place, the works of the author whose principal thread is her native city, Córdoba, will be analyzed. Along with this unifying thread, other elements –objects, literary devices, or characters– that act as a link in these and other works of this hidden Andalusian writer will also be delved into. This study will also address the works in which Emily Santa-Cruz cultivated the genre of detective fiction so as to examine, likewise, the common threads they share, among which are the figure of the main character and the didactic role that all the stories assume. With this analysis it is intended to bring this author to the fore and explore the common elements with which she wanted to interrelate much of her production in order to give unity to her work.